Hieracium terraccianoi (Asteraceae), a new species endemic to the Pollino National Park (Southern Italy) - Di Gristina, Emilio; Gottschlich, Günter; Raimondo, Francesco Maria (Phytotaxa, 2014)
A new species endemic to the Pollino National Park (Southern Italy), Hieracium terraccianoi, is described and illustrated. Information on its morphology, distribution, ecology and taxonomic relationships is provided.